2021
DOI: 10.1001/jamapsychiatry.2021.1715
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and Cost-Benefit of Onsite Contraceptive Services With and Without Incentives Among Women With Opioid Use Disorder at High Risk for Unintended Pregnancy

Abstract: IMPORTANCERates of in utero opioid exposure continue to increase in the US. Nearly all of these pregnancies are unintended but there has been little intervention research addressing this growing and costly public health problem.OBJECTIVE To test the efficacy and cost-benefit of onsite contraceptive services with and without incentives to increase prescription contraceptive use among women with opioid use disorder (OUD) at high risk for unintended pregnancy compared with usual care. DESIGN, SETTING, AND PARTICI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
25
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(29 citation statements)
references
References 33 publications
3
25
1
Order By: Relevance
“…Our findings suggest that this is indeed the case because 100% of the 17 women who opted for a MOUD referral started MOUD within 30 days of study enrollment. Thus, findings from the pilot both corroborate and extend the findings reported by Heil and colleagues 22 …”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…Our findings suggest that this is indeed the case because 100% of the 17 women who opted for a MOUD referral started MOUD within 30 days of study enrollment. Thus, findings from the pilot both corroborate and extend the findings reported by Heil and colleagues 22 …”
Section: Discussionsupporting
confidence: 90%
“…Also, as a pilot study, the use of a one‐arm design greatly limits any inference relative to causality. Noteworthily, however, is that in the control arm of the study reported by Heil and colleagues 22 none of the women reported having a LARC implant in the subsequent 12 months. Although we cannot assume a value of zero as a likely outcome of not providing the EMC intervention to women with OUD, the obtained uptake of 40% suggest a robust intervention effect is likely to be found in the context of adequately powered RCT.…”
Section: Discussionmentioning
confidence: 89%
See 2 more Smart Citations
“…Recent research shows that providing either face-to-face or computerized RSH services using a shared decision making approach, between provider and patient, to non-pregnant women receiving MOUD hold promise for increasing both decision making and follow through on a contraceptive practice decision compared to usual care ( 6 ). Increasing access to person-centered contraceptive counseling through co-located RSH services can help better fulfill the health needs of this patient population and have been shown to be cost effective ( 23 ).…”
Section: Discussionmentioning
confidence: 99%